Molecular and pharmacological mechanisms of gupercoagulation stimulation by means of peropal and transdermal estrogen forms - O A Gromova; I Yu Torshin; N K Tetruashvili; O A Limanova; V N Serov (IP Berlin A.V., 2014)
This paper presents the results of a molecular pharmacologicalanalysis of prothrombotic effects of oral estrogen drugs,as well asthe actual problem resoving methods of bioinformatics and systems biology. At the same time, the transdermal administration of estrogensallows not only to maintain a stable blood concentration, but alsoalmost completely avoid liver metabolism. Transdermal estrogen ischaracterized by pronounced pharmacokinetic advantages that can reducethe dosage of estrogen without losing effectiveness; avoidingundesirable effects of excessive activation of blood coagulation.